Antibacterial Potential Of The Aqueous And Organic Extracts Of Bixa Orellana L. - P. SUMATHI; A. PARVATHI (International Journal of Pharma and Bio Sciences, 2011)
Bixa orellana is valued for its food and medicinal uses. It is considered as a good remedy for treating dysentery and kidney diseases. The present study dealt with antibacterial potential of the crude aqueous and organic extracts from leaves, seeds and empty seed capsules of Bixa orellana against one Gram-positive and three Gram-negative bacteria by using agar diffusion method. The leaf extracts of methanol, dimethyl sulphoxide, ethanol and acetone exhibited potential and significant antibacterial activity against Staphylococcus aureus at 800, 1600; 1600 and 3200 µg/ml, respectively. However, none of the aqueous extracts showed antibacterial activity against the tested bacteria. The extracts of dimethyl sulphoxide and methanol from empty seed capsules also showed effective antibacterial activity against Staphylococcus aureus and Salmonella typhi at 3200 and 800 & 3200 µg/ml, respectively. Various solvents and aqueous extracts of the seeds did not show any appreciable antibacterial activity except in dimethyl sulphoxide solvent extracts. Moderate growth inhibition zone of Salmonella typhi and Staphylococcus aureus in dimethyl sulphoxide was noticed at high concentrations of 6400µg/ml.